Self-Help Group and Rural Women’s Socioeconomic Empowerment in India: An SDG Perspective - Maitrayee Rout; Suraj Agrawal; Shiv Ram Pattnaik (International Journal of Rural and Regional Development, 2026)
This research examines the impact of Self-Help Groups (SHGs) on rural women in Khurda District, Odisha, and their contribution to achieving the United Nations’ Sustainable Development Goals (SDGs). The central aim of the study is to understand whether participation in SHGs helps women improve their socioeconomic conditions and move closer to global development goals, such as poverty reduction, food security, better health, improved education, and gender equality. To assess this, the study compares the living conditions of women before and after joining SHGs using data collected through a large-scale survey. The research focuses on three key areas: changes in the socioeconomic background of the women, improvements in their income and savings, and their level of awareness about legal and social rights. By examining these factors, the study highlights the broader role SHGs play in empowering rural women and strengthening community development The findings show that SHGs have a significant positive impact on women’s lives. Women who became members of SHGs and received financial assistance were able to start small businesses and income-generating activities. This helped them increase their earnings and build financial stability through regular savings. Beyond economic benefits, participation in SHGs also improved women’s confidence, self-respect, and decision-making power within their households Moreover, women involved in SHGs reported greater awareness of their rights and increased participation in community activities. They felt more comfortable working outside the home, interacting with others, and contributing to family and social decisions. These changes demonstrate that SHGs do more than provide financial support—they create opportunities for social empowerment and personal growth. The study concludes that Self-Help Groups are an effective tool for empowering rural women. By improving economic independence, awareness, and social participation, SHGs contribute not only to individual and family well-being but also to broader community development and progress toward sustainable development goals.
Keywords: Microcredit India; rural women; self-help groups; socioeconomic development; sustainable development goals (SDGs)